PENERAPAN ALGORITMA AES PADA KEAMANAN URL STUDI KASUS WEBSITE MAHASISWA ATMA LUHUR - indriati, asih (Himpunan Dosen Ilmu Komputer, 2023)
AES is a standard encryption method that uses a symmetric key and consists of three encoding blocks: AES-128, AES-192, and AES-256. The method was first published as Rijndael. The Atma Luhur student website contains several pages that can be accessed by clicking on Links, which provide student academic data such as photos and grades. When accessing any of these pages, a URL is formed by specifying the relevant File, This creates a vulnerability whereby the File can be targeted by attacks. To secure the URL of Atma Luhur's student website, this study recommends using the AES algorithm to encrypt the intended URL. We carried out tests on 34 URLs of the Atma Luhur student website and achieved a 100% encryption level. To collect data in this study, we employed observation, interviews, and a literature study. We developed the system in an iterative way, involving analysis, design, implementation, and testing. The iterative method comprises the stages of analysis, design, implementation, and testing. In system development, the author also uses the OOP (Object Oriented Programming) method. The test results from 34 URLs of the Atma Luhur student website indicate a 100% encryption level. Keywords: AES, Kriptografi, URL